From world war to cold war : churchill, roosevelt, and the international history of the 1940s - Reynolds, David (Oxford University Press, 2010)
The 1940s was probably the most dramatic and decisive decade of the twentieth century. In this volume, the leading international historian David Reynolds has brought together a collection of incisive essays, five of them previously unpublished, to explore some of the major themes, events, and personalities of this pivotal decade.